Effect of replacing dietary fish oil with vegetable oils on the fatty acid composition of muscle tissue of juvenile California halibut (Paralichthys californicus) - D Badillo-Zapata; G Correa-Reyes; LR D'Abramo; JP Lazo; JF Toro-Vázquez; MT Viana (Ciencias Marinas, 2010)
Total replacement of cod liver oil by vegetable oils in the diets of juvenile California halibut (Paralichthys californicus) was analyzed. Five diets were formulated with olive oil, corn oil, linseed oil, and two combinations of linseed oil and corn oil, and compared with a control diet containing cod liver oil during a 12-week feeding experiment. Highest growth was observed in fish fed the control diet; however, no significant differences in growth and survival were observed among the dietary treatments. The fatty acids from linseed, corn, and olive oils were the most accumulated in the tissue, increasing in proportion to the total fatty acids. Reduced levels of 20:5n-3 and 20:4n-6 in the presence of high dietary levels of 18:3n-3 and 18:2n-6 suggest that, as in most marine fishes, synthesis of 18:3n-3 to 20:5n-3 and of 18:2n-6 to 20:4n-6 is either very limited or does not occur. Although the content of 22:6n-3 in the muscle of fish fed the control diet was approximately 2.0 to 2.5 times greater than that in the muscle tissue of fish fed the experimental diets, no significant differences were detected. A proportional decrease in 20:5n-3 among all fatty acids and a lack of an increase in body tissue suggest that this fatty acid was being used to synthesize 22:6n-3. The significant reductions in the level of 20:5n-3 indicate that if the experiment had been conducted over a longer period of time, a level would eventually be reached whereby the dietary deficiency would presumably be reflected by an adverse effect on growth. Additional research is needed, particularly regarding the proportional and quantitative changes of 20:5n-3 and 22:6n-3 in the composition of the muscle tissue.